Letterhead & logo design 11 - Design Army (Beverly : Rockport Publishers, 2012)
Design Army, based in Washington, D.C., has collected and curated this latest collection of stunning letterheads and logos. Known for their streamlined design style, Design Army selected a stunning collection for this bestselling Letterhead and Logo series. Letterhead and Logo Design 11 is an invaluable resource containing hundreds of inspirational logos and letterheads designers will refer to again and again.
Keywords: Logo's ; grafische vormgeving